Necessary Qualities of Prophets (Honesty, Truthfulness, Delivery, and Discreetness as a model): A Doctrinal Study - Al-Nwihi , Mohammed Khalil (Dirasat: Shari'a and Law Sciences, 2021)
This study aims to introduce the prophet and the messenger in the language and terminology and to indicate some of the qualities that the prophets and messengers (peace and blessings of Allaah be upon them) should have. The study also aims to identify the mental and mental evidence and proofs that indicate the proof of these duties for the apostles and prophets, peace be upon them. The researcher used the analytical method by presenting a set of qualities that should be attributed to the prophets and apostles (peace be upon them), mentioning the evidence and proofs, standing on their details, and pointing out their intent. The study came to the following conclusions: there must be several qualities and perfections in the right of the prophets and messengers (peace and blessings of Allaah be upon them), such as honesty, truthfulness, reporting, virtuousness, and others. It also became clear after studying these duties with their evidence that what was attributed to the prophets and apostles-peace and blessings of Allaah be upon them - of sins, whether great or small, is nothing but pure slander and lies. The study recommended that scholars, especially specialists, should pay attention to the statement of what is necessary, what is impossible, and what is permissible in the case of the prophets and apostles (peace and blessings of Allaah be upon them). And pay attention to the evidence and proofs that prove that these duties are obligatory for the prophets and messengers –peace be upon them-.